Successful pregnancy of an SMA type 3 sitter on Nusinersen therapy - a case report - Miriam Hiebeler; Simone Thiele; Maggie C. Walter (BMC Neurology)
Abstract Background Due to improved treatment options, more SMA patients reach childbearing age. Currently, limited data on pregnant SMA patients is available, especially in relation to disease-modifying therapies (DMT). This case report helps to elucidate new approaches for future guidelines in the management of pregnancy and SMA. Case Report A 33-year-old wheelchair-bound patient with SMA type 3 (sitter) became pregnant following 36 months of Nusinersen treatment. The last dose was administered in the third gestational week. After pregnancy was confirmed, therapy was stopped immediately. A healthy child was born in the 34th gestational week by caesarean section. After a short nursing period, Nusinersen was restarted 6 weeks after the expected gestational date. At this time, the patient reported deteriorated motor functions, which stabilized at a lower level compared to pre-pregnancy in the 2-year follow-up, despite restarting Nusinersen treatment. Discussion So far, only few cases of successful pregnancies of SMA patients on DMT have been reported. In natural history, the majority of patients experienced an increased deterioration of motor function while fetal outcome was not impaired. Our case shows that although Nusinersen treatment was applied in the third gestational week prior to proof of pregnancy, outcome was positive for mother and child. Future studies will have to determine whether ongoing treatment with Nusinersen during pregnancy should be recommended.